2021
DOI: 10.1111/jgh.15694
|View full text |Cite
|
Sign up to set email alerts
|

Low fermentable oligosaccharides, disaccharides, monosaccharides, and polyols dietversustraditional dietary advice for functional dyspepsia: a randomized controlled trial

Abstract: Background and Aim Prospective trials evaluating efficacy of specific diet restriction in functional dyspepsia (FD) are scarce. We aimed to assess efficacy of low fermentable oligosaccharides, disaccharides, monosaccharides, and polyols (FODMAP) diet in FD, compared with traditional dietary advice (TDA). Methods In this prospective, single‐blind trial, patients with FD (Rome IV) were randomized into low FODMAP diet (LFD) and TDA groups, for 4 weeks (phase I). In phase II (4–12 weeks), LFD group was advised sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 39 publications
0
33
0
1
Order By: Relevance
“…Additionally, in a prospective, single-blind trial, 105 patients diagnosed with FD by Rome IV criteria were randomized into two groups low FODMAP diet ( n = 54) and traditional diet advice groups ( n = 51), for four weeks [ 26 ]. In a second phase, for the next eight weeks, the LFD group were re-exposed to FODMAPs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, in a prospective, single-blind trial, 105 patients diagnosed with FD by Rome IV criteria were randomized into two groups low FODMAP diet ( n = 54) and traditional diet advice groups ( n = 51), for four weeks [ 26 ]. In a second phase, for the next eight weeks, the LFD group were re-exposed to FODMAPs.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, patients with post-prandial distress syndrome or bloating had a higher response rate to low FODMAP diet ( p = 0.04). Both interventions improved SF-NDI quality of life scores and multivariate analysis revealed that bloating and male gender were factors predicting response to LFD [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A beneficial effect of a low FODMAP diet compared with standard dietary advice was reported in a cohort of 59 patients with FD, but with 81% having coexisting IBS ( 67 ). Goyal et al ( 68 ) compared the effect of a 4-week low FODMAP diet to traditional dietary advice in a group of 105 patients with Rome IV FD where those with overlapping IBS and other dietary-related conditions (e.g., a history of lactose/fructose intolerance and patients already on restricted diet) were excluded. Symptoms improved in 67% after a low FODMAP diet compared with 57% after traditional dietary advice, mainly in the PDS subgroup and without significant difference between diets.…”
Section: Dietary Interventionsmentioning
confidence: 99%